(untitled) (Research, Society and Development, 2021)
The global economy is directly dependent on fossil fuels, consuming a total of approximately 70% of these energy sources. However, renewable energies, especially biofuels produced by biomass, are gaining ground, with emphasis on elephant grass, which has been standing out in the production of bioethanol in Brazil. However, before fermentation takes place for the production of bioethanol, the biomass must undergo a process called pre-treatment. Therefore, when analyzing the chemical processes, the optimization of the variables for the pre-treatment is essential, thus the need to apply a mathematical modeling system such as fuzzy or fuzzy logic arises. Given this context, the objective of this article is to identify how the state of knowledge about the application of fuzzy logic in the alkaline pre-treatment of elephant grass is configured. By conducting the research using the Systemic Literature Review (RBS), it was possible to identify several opportunities for the application of fuzzy logic in alkaline pre-treatments in elephant grass. Of the 86 documents analyzed in this research, 100% were from research and bibliographic review articles, which demonstrates the relevance in academia of the use of elephant grass in the production of bioethanol and, in the same way, research on the application of pre- Biomass treatment has gained importance in recent years, being increasingly studied and developed by researchers in the area. Although it does not present any article with specific reference to the use of fuzzy logic in the alkaline pre-treatment of elephant grass, this opens up a wide range for further research using fuzzy logic.